Being Biblical? Slavery, sexuality, and the inclusive community - Burridge, Richard A. (HTS teologiese studies, 2008)
The use of the Bible in ethical debate has been central for the last two millennia. Current debates about sexuality, or the position of women in church leadership, are marked by both, or all, sides of the argument using Scripture. However, this has been true of many issues in the past. This is demonstrated in the debate about slavery two hundred years ago. Careful analysis of the use of Scripture in both the justification and critique of apartheid reveals how both sides quoted Scripture in its various modes, such as rules, principles, paradigms, and overall world-view. The biographical nature of the Gospels means that we must set Jesus’ rigorous ethical teaching in the context of the narrative of his deeds, including his open and welcoming acceptance of all people. It was an inclusive community of interpretation which changed the debates about slavery and apartheid, and a similar inclusive community is needed today.